2018
DOI: 10.1097/dad.0000000000000915
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Elafin in Dermatitis Herpetiformis

Abstract: Under normal circumstances, keratinocytes overexpress elafin to downregulate a neutrophil mediated inflammatory response. The deficient expression of elafin in the aforementioned probed DH specimens correlates with previous similar elafin underexpression in intestinal samples of active CD. These histological findings suggest that these 2 gluten mediated disorders carry an abnormal elafin underexpression during disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…In our previous studies, we found that the oral traditional Chinese medicine, YinXieLing, exerts its therapeutic effect on psoriasis by inhibiting of cell proliferation and pro-inflammation while increasing CD4+ Foxp3+ regulatory t cell generation 39-41. These results align well with previous studies that show that PI3 downregulates neutrophil-mediated inflammation and IFNG inhibits neutrophil accumulation 56-59.…”
Section: Discussionsupporting
confidence: 89%
“…In our previous studies, we found that the oral traditional Chinese medicine, YinXieLing, exerts its therapeutic effect on psoriasis by inhibiting of cell proliferation and pro-inflammation while increasing CD4+ Foxp3+ regulatory t cell generation 39-41. These results align well with previous studies that show that PI3 downregulates neutrophil-mediated inflammation and IFNG inhibits neutrophil accumulation 56-59.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study demonstrated a down-regulation of elafin, a serine protease inhibitor that inhibits a neutrophil mediated inflammatory response, in keratinocytes from DH skin. A similar finding could be also found in the epithelial cells from the small bowel of patients with active CD (124).…”
Section: Pathogenesissupporting
confidence: 79%
“…Furthermore, PI3, FOSL1 and CXCL1 were each found to interact with CXCL8 following the construction of the protein interaction network of the four genes. The PI3 gene is a serine protease inhibitor that can inhibit excessive damage to elastase released by neutrophils during the inflammation process to resist the inflammatory response, antiviral and immunomodulatory effects (26)(27)(28)(29)(30). It has been previously reported that PI3 levels are increased in the blood of children with AD (31).…”
Section: Discussionmentioning
confidence: 99%